PERAN GURU DALAM MENANAMKAN PERILAKU SOPAN SANTUN ANAK USIA 5-6 TAHUN DI RA RABBANI KABUPATEN BONE - Hatmala Citra, Detsy; Syam, A. Sri Mardiyanti (EDUCHILD (Journal of Early Childhood Education), 2024)
This study discusses the Role of Teachers in Instilling Polite Behavior in Children Aged 5-6 Years in RA Rabbani, Tanete Riattang District, Bone Regency. The purpose of this study is to determine the role of teachers in instilling polite behavior in children aged 5-6 years and to determine the description of polite behavior in children aged 5-6 years in RA Rabbani, Tanete Riattang District, Bone Regency. The type of research used is qualitative descriptive with a research approach using a qualitative, pedagogical and psychological research approach. This study uses data analysis techniques with the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that there are three descriptions of polite behavior in children aged 5-6 years in RA Rabbani, Tanete Riattang District, Bone Regency, namely a) Mutual respect, an attitude of caring in treating others politely without lowering one's own self-esteem. b) Saying thank you, a way to show that you appreciate the time and effort that others give. c) Socializing, a process that can provide the values needed for the formation of attitudes and personality. Furthermore, there are three roles of teachers in instilling polite behavior in children aged 5-6 years at RA Rabbani, Tanete Riattang District, Bone Regency, namely a) teachers as educators are people whose job is to direct, guide, teach, care for, and train students. b) Teachers as educators, play a role in helping intellectual, affective, and psychomotor development, through the delivery of knowledge. c) Teachers as mentors, are expected to be able to provide guidance services to children.